Online Resources: Digital Materials: China and Japan. (Religious Studies Review (John Wiley & Sons, Inc.), 2020)
The article reviews several websites including "https://www.religiousstudiesproject.com/" from The Religious Studies Project, "https://bulletin.equinoxpub.com/ from Religion Bulletin", and "www.cosmologicsmagazine.com" from Cosmologics Magazine.